The Sense of Belonging in School from the Perspective of Students with Developmental Difficulties - Vesna S. Radovanović; Jasmina M. Kovačević (University of Belgrade, Teacher Education Faculty, 2021)
The success of inclusive education, measured by the students' sense of belonging in school, has recently become the subject of numerous foreign research papers, while a modest number of papers on this topic can be found in our literature. Given that inclusive education has been present in our country for a decade, the aim of the research was to determine the level of the sense of belonging in a school environment of children with developmental difficulties in an inclusive environment. The sample consisted of 35 children with developmental difficulties from 11 primary schools in which inclusive education has been implemented for at least eight years. The research used the Sense of Belonging in School Scale adapted for the needs of the research with children with developmental difficulties. The results of the research obtained by the scaling technique showed that the majority of the students have a high level of the sense of belonging in their school, and no statistically significant difference was found in relation to the type of developmental difficulty. The highest degree of agreement with the statements was found in students with physical and sensory disorders, followed by students with intellectual disabilities, then disorders within the spectrum of autism, while students with behavioral difficulties agreed the least with the claims. The obtained results indicate a positive experience of students during schooling in inclusive classes.